Assessment of conservation status of riparian vascular plant species in a dry season exposed flood plain area of the Incalaue river catchment, Niassa Special Reserve, Northern Mozambique - Ezrah Natumanya; Natasha Ribeiro; Majaliwa Jackson-Gilbert Mwanjalolo; Franziska Steinbruch (Environmental Research: Ecology, 2023)
Riparian vegetation usually gets less focus in biodiversity assessments and yet species diversity is important knowledge when applying patch specific conservation value in the Niassa Special Reserve (NSR). This study assessed the composition and conservation status of riparian species in an exposed river basin downstream location. Purposive sampling was used in the selection of sites and respondents to maximize data collection. The study found 19 species belonging to 15 families with 52.63% of them having a frequency of ⩾50% in sampling plots. There were 10 species that are endemic to the sub-Sharan Africa Region. Fabaceae was the dominant family with 5 species. The species with the highest population was Flacourtia indica (Burm. f.) Merr. Species richness ranged from 0.35 to 0.98 with a mean of 0.66 ± 0.22. The IVI ranged from 34.70 ( F. indica (Burm. f.) Merr) to 4.43 ( Tribulus cistoides L.) with a mean of 15.79 ± 7.79. Threats of species loss and ecosystem disturbance were agriculture, infrastructure development and plant harvests. There was a reported decline in species availability over the previous 10 years by 18.7% of the respondents. The results added to existing studies and records of vegetation species of conservation value in areas exposed to loss in the NSR. This study advances research on vegetation range dynamics in the NSR and presents a need to mitigate human land use impacts on riparian vegetation species composition.